Microbial characteristics of dental caries in HIV positive individuals - Kalanzi, Dunstan; Mayanja-Kizza, Harriet; Nakanjako, Damalie; Semitala, Fred; Mboowa, Gerald; Mbabali, Muhammad; Kigozi, Edgar; Katabazi, Fred Ashaba; Sserwadda, Ivan; Kateete, David P.; Achan, Beatrice; Sewankambo, Nelson K.; et al. (Frontiers in Oral Health, 2022)
Background Dental caries is a multifactorial disease that affects many people. Even though microorganisms play a crucial role in causing dental caries, diagnosis is routinely macroscopic. In order to improve early detection especially in HIV patients who are disproportionately affected, there is need to reconcile the macroscopic and microscopic characteristics of dental caries. Therefore, the aim of this study was to characterize the oral microbiota profile along the decayed, missing, filled teeth (DMFT) index using amplicon sequencing data. Methods Amplicon sequencing of the V6-V8 region of the 16S rRNA gene was done on DNA recovered from whole unstimulated saliva of 59 HIV positive and 29 HIV negative individuals. The microbial structure, composition and co-occurrence networks were characterized using QIIME-2, Phyloseq, Microbiome-1.9.2 and Metacoder in R. Results We characterized the oral microbiota into 2,093 operational taxonomic units (OTUs), 21 phyla and 239 genera from 2.6 million high quality sequence reads. While oral microbiota did not cluster participants into distinct groups that track with the DMFT index, we observed the following: (a) The proportion of accessory microbiota was highest in the high DMFT category while the core size (∼50% of richness) remained relatively stable across all categories. (b) The abundance of core genera such as Stomatobaculum, Peptostreptococcus and Campylobacter was high at onset of dental caries, (c) A general difference in oral microbial biomass. (d) The onset of dental caries (low DMFT) was associated with significantly lower oral microbial entropy. Conclusions Although oral microbial shifts along the DMFT index were not distinct, we demonstrated the potential utility of microbiota dynamics to characterize oral disease. Therefore, we propose a microbial framework using the DMFT index to better understand dental caries among HIV positive people in resource limited settings.